Sources of Information, Training Needs, Preparation and Response to Disaster of Selected Communities in Central Luzon, Philippines - Asio, John Mark (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2021)
Nature has its due course and disaster is always an aftermath of a catastrophic event. The purpose of this study is to assess the sources of information, training needs, preparation, and response of the community to disaster. To achieve this purpose, the study used a descriptive design with the survey as the instrument for data gathering. For the respondents, 136 individuals took part in the survey which took two months to accommodate. The researcher created a simple survey instrument and subjected it to reliability and validity tests. In analyzing the data, the researcher used weighted mean, standard deviation, t-test, and analysis of variance. Results showed that the radio is the most common source of information to disaster. Respondents emphasized the need for disaster training in the community and they also indicated that they partially observed the preparation and response in their communities. At the same time, there were significant differences observed in the sources of information, training needs, preparation, and response to the disaster of the respondents when grouped according to their communities. Furthermore, a significant difference emerged in the training needs when grouped according to the members of the family. Based on the results, the researcher recommends a community disaster preparation enhancement program for the involved communities in the study.